Evaluating the Role of National Commission for Human Development and Primary Education in Khyber Pakhtunkhwa, Pakistan - Muhammad Suleman Nasir; Abdul Majeed; Muhammad Qayyum Ahsan (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
The purpose and aim of the National Commission for Human Development (NCHD) are to develop the opportunity of struggles through Pakistan's government in safeguarding the operative delivery of communal services. The main purpose is to evaluate the role of NCHD in the advancement of the primary level of education in Khyber Pakhtunkhwa, Pakistan. The survey type descriptive research methodology was used to attain the objectives of the study. All Government boys’ primary school teachers and NCHD staff members set up the population of this study. The study’s sample was taken from the four randomly chosen districts, i.e., Bannu, Lakk Marwat, Karak, and Dera Ismail Khan of Khyber Pakhtunkhwa province. The data was collected from 200 teachers and 100 staff members from NCHD staff from the particular districts through a questionnaire using a simple random sampling technique. Data were examined using Mean, Standard Deviation, and t-test was used to examine the data. It is inferred that the NCHD was playing its active role in increasing enrollment and in reducing the dropout in the schools at the primary level. It was also concluded that advanced plans of NCHD are meaningfully promoting primary education in Khyber Pakhtunkhwa. This study recommends that NCHD should organize extra training workshops and talks for teachers at the primary level concerning the student’s assessment for better education and to make them updated and skilled.